Brain Hemodynamic Intermediate Phenotype Links Vitamin B12 to Cognitive Profile of Healthy and Mild Cognitive Impaired Subjects. (2nd June 2019) - Cecchetti, Luca; Lettieri, Giada; Handjaras, Giacomo; Leo, Andrea; Ricciardi, Emiliano; Pietrini, Pietro; Pellegrini, Silvia; ,
Abstract : Vitamin B12, folate, and homocysteine are implicated in pivotal neurodegenerative mechanisms and partake in elders' mental decline. Findings on the association between vitamin-related biochemistry and cognitive abilities suggest that the structural and functional properties of the brain may represent an intermediate biomarker linking vitamin concentrations to cognition. Despite this, no previous study directly investigated whether vitamin B12, folate, and homocysteine levels are sufficient to explain individual neuropsychological profiles or, alternatively, whether the activity of brain regions modulated by these compounds better predicts cognition in elders. Here, we measured the relationship between vitamin blood concentrations, scores at seventeen neuropsychological tests, and brain activity of sixty-five elders spanning from normal to Mild Cognitive Impairment. We then evaluated whether task-related brain responses represent an intermediate phenotype, providing a better prediction of subjects' neuropsychological scores, as compared to the one obtained considering blood biochemistry only. We found that the hemodynamic activity of the right dorsal anterior cingulate cortex was positively associated (p   value < 0.05 cluster corrected) with vitamin B12 concentrations, suggesting that elders with higher B12 levels had a more pronounced recruitment of this salience network region. Crucially, the activity of this area significantly predicted subjects' visual search and attention abilities (p   value = 0.0023 ), whereas B12 levels per se failed to do so. Our results demonstrate that the relationship between blood biochemistry and elders' cognitive abilities is revealed when brain activity is included into the equation, thus highlighting the role of brain imaging as intermediate phenotype.